The Institutional Catholic Church in Poland on European Integration - Machaj, Łukasz; Białas-Zielińska, Klaudyna (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
Representatives of the institutional Catholic Church in Poland have carefully observed the process of European integration since its beginnings in the mid-twentieth century. The bishops seemed to think that the very idea of integration remains in agreement with the basic tenets of Catholic social teaching, such as the principles of solidarity, subsidiarity and thecommon good. Nevertheless, the particular form of integration implemented in contemporaryEurope often raises their serious concerns. For obvious reasons, any detailed examination of these issues was impossible under the Communist regime; only its fall created an opportunity for any systematic evaluation of the matter. The paper presents the positions taken by institutional Catholic Church in Poland – mainly by the Polish Episcopal Conference (PEC) – on the question of European integration and Poland’s accession to the European Union from 1989 until today. The authors contend that the hierarchs’ official view of these processes was – generally speaking – favorable, though permeated with many reservations concerning the EU’s approach to some issues of religious and moral importance.
Keywords: Kościół katolicki; integracja europejska